Clinical Analysis Of The Impact Of Social Media On The Mind Of Young People - Dehkanov, Sherzod Munavvarovich (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This thesis analyzes the relationship between the use of social media and low self-esteem and mental instability in young people from a clinical perspective. The results showed that young people who are active on social media for more than four hours a day have a significant decrease in self-esteem, increased depressive symptoms and anxiety. In particular, the impact of visual platforms such as Instagram and TikTok has more negative consequences. According to the results of the study, social comparison mechanisms, cyberbullying phenomena and the development of the "live to see" syndrome play a key role in increasing the mental instability of young people.